Determining the impact of orthodontic patients' characteristics on their usage and preferences of social media - Al-Gunaid, Talat H. (J Taibah Univ Med Sci, 2020)
OBJECTIVE: This study aims to assess the impact of orthodontic patients' characteristics on their usage and personal preferences of social media. METHODS: We developed a descriptive cross-sectional study. The questionnaire contained demographic data and questions about the usage of social media and their preferred platforms. The validity and reliability of the questionnaire were examined. The final Arabic version was adopted, and Google Drive was used to conduct the survey. The survey link was sent to the general public via different social media platforms and applications. RESULTS: A total of 477 respondents participated in this study, which included 274 women and 203 men. Significant variation in the use of social media was observed between the genders. The use of Twitter, Snapchat, and YouTube was significantly higher in the 21–30-year-old group than in the other groups. Instagram was favoured by the 13–20-year-old group, while WhatsApp was most frequently used by those aged around 40 years. Social media usage was significantly more apparent among university graduates in both the orthodontic and non-orthodontic groups. The use of Twitter, Snapchat, YouTube, Instagram, and WhatsApp was significantly more common in the medium-income group than in any other group. Snapchat was the most commonly used platform across both groups. CONCLUSION: Our study revealed that Twitter, Snapchat, and YouTube were the preferred social media applications for the middle-aged group. The use of Instagram was greatest in the teenage group, while WhatsApp was favoured by the older groups. Social media usage was most prevalent among university graduates, regardless of whether they were orthodontic or non-orthodontic patients.